PO17 Contribution to the chemical study of the bioactive compounds of Streptomyces 5.1 against the phytopathogen Colletotrichum gloeosporioides: A chemical approach in the search for natural antifungal agents - Jaimes Cáceres, Edison Javier; Castellanos Hernández, Leonardo; Ramos Rodríguez, Freddy Alejandro (Revista Productos Naturales, 2025)
The present study aimed to analyze the extracts from the culture of Streptomyces 5.1 to identify the metabolites responsible for the antifungal activity observed against the phytopathogen Colletotrichum gloeosporioides, which affects avocado crops and causes significant economic losses [1; 2]. The methodology involved culturing the microorganism in two different media (M3.7 with salts and GYM [3] at a scale of 15 liters, followed by an evaluation of the antifungal activity of the obtained extracts.